La reconnaissance académique de l’engagement bénévole des étudiants - Julie Testi (Éducation et Socialisation)
This paper questions instead of non-formal learning in university courses. In the way of Bologna process and LRU's law (2007), orientation and professionalization are integrated in universities’ missions. The establishment of these new missions translates by the growth of competencies approach in courses and by enhancement of activities that develop soft skills. From the example of AFEV (Association de la Fondation Étudiante pour la Ville), we show how recognition of student volunteering is developed in university courses. This article also shows how associations participate to create tools for evaluate soft skills to register as an experience of students’ professionalization.